The Common Retention Practices Among Orthodontists from Different Countries - Mohammed Almuzian; Samer Mheissen; Haris Khan; Fahad Alharbi; Emad Eddin Alzoubi; Mark Brian Wertheimer (Galenos Yayinevi, 2024)
Objective: To investigate the most common retention practices, factors influencing the retention protocol, and the differences among orthodontists regarding retention practices. Methods: An online validated questionnaire was anonymously sent to 3,000 orthodontic residents and clinicians. The survey consisted of 19 questions regarding the participants' demographics, prescribed retention appliances, factors affecting retention appliance choices, and adjunctive retention procedures. Descriptive statistics, Chi2 and Kendall's Tau-b tests were applied. Results: Five hundred fifty-five orthodontic residents and clinicians, 53.3% males and 46.7% females, completed the survey, indicating a response rate of 18.5%. Although participants' demographics, type of treatment and pre-treatment malocclusion influence the choice of retention protocols, thermoplastic retainers (TR) were the most popular retention regime for the maxillary arch for both adults (47.4%) and adolescents (42.3%). Bonded retainers (BR) were the favored option for the mandibular arch (44.9% of adults and 40.7% of adolescents). The degree of arch expansion (64.1%) and the degree of interdigitation (50.1%) after treatment were the most influential factors for the choice of the preferred type of retainers by the respondents. 68.6% of the participants thought professional retention guidelines would be useful. Conclusion: Thermoplastic retainers were the most common retention appliances for adults and adolescents in the maxilla. At the same time, BR was the most favored retainer in the mandibular arch, with clinical experience, practice setting, and malocclusion- and treatment-related factors influencing the type of the chosen appliance. The demographic differences and the uneven participation in the survey need to be considered while interpreting the findings of this study.